Intravenous Thrombolysis For Acute Ischemic Stroke in Fabry Disease. Issue 5 (September 2019) - Kargiotis, Odysseas; Psychogios, Klearchos; Safouris, Apostolos; Kalyvas, Pericles; Magoufis, Georgios; Stamboulis, Eleftherios; Tsivgoulis, Georgios
Abstract : Introduction: Fabry is a rare X-linked recessive genetic disease caused by α-galactosidase A deficiency. Cerebrovascular events occur in ∼13% of patients, whereas stroke may be the presenting clinical manifestation. There are very limited case reports of tissue plasminogen activator administration for acute ischemic stroke in patients with Fabry disease. Case report: A 46-year-old man presented with right-sided hemiparesis with a National Institutes of Health Stroke Scale score of 3. Brain computed tomography showed a hyperdense lesion resembling carvenous angioma. The patient received intravenous thrombolysis 265 minutes after symptom onset, with clinical improvement (discharge National Institutes of Health Stroke Scale score of 1). Brain magnetic resonance imaging disclosed acute thalamic infarction, cavernous angioma, and multiple cerebral microbleeds. The presence of skin angiokeratomas and cardiac hypertrophy prompted further positive investigation for Fabry disease (nondetectable α-galactosidase activity, excessively elevated lyso-Gb3, and pathogenic deletion in the GLA gene). Conclusion: The present case supports the scarce data underscoring the safety of intravenous thrombolysis for acute ischemic stroke in Fabry disease patients even when cerebral microbleeds are present.